Comparative analysis of modern authentication and authorization protocols for web applications - Vasylenko, Ostap (Національний технічний університет "Харківський політехнічний інститут", 2025)
The subject of study in this article is a set of widely used authentication and authorization protocols, including Basic Authentication, OAuth 1.0, OAuth 2.0, Single Sign-On (SSO), and Multi-Factor Authentication (MFA). The purpose of the article is to compare these technologies in terms of security, scalability, integration complexity, and suitability for various IT environments. The research is based on the analysis of official standards (RFCs, NIST guidelines, OASIS specifications) and industry practices. The results demonstrate that traditional approaches, such as Basic Auth and OAuth 1.0, are becoming obsolete due to limited security, while OAuth 2.0 combined with SSO provides a balance between user convenience and security. The introduction of MFA significantly enhances protection against account compromise but increases implementation complexity. Conclusion. No single protocol is a universal solution; the highest security level is achieved through a combination of modern authorization protocols, multi-factor authentication, token encryption, and Zero Trust principles. These findings can be applied by developers, system architects, and cybersecurity specialists to design and implement robust authentication and authorization systems capable of addressing current and emerging digital security challenges. Предметом дослідження в даній статті є набір широко використовуваних протоколів автентифікації та авторизації, включаючи Basic Authentication, OAuth 1.0, OAuth 2.0, Single Sign-On (SSO) та Multi-Factor Authentication (MFA). Метою статті є порівняння цих технологій з точки зору безпеки, масштабованості, складності інтеграції та придатності для різних ІТ-середовищ. Дослідження базується на аналізі офіційних стандартів (RFC, рекомендації NIST, специфікації OASIS) та галузевих практик. Результати демонструють, що традиційні підходи, такі як Basic Auth та OAuth 1.0, застарівають через обмежену безпеку, тоді як OAuth 2.0 у поєднанні з SSO забезпечує баланс між зручністю та безпекою користувача. Впровадження багатофакторної автентифікації (MFA) значно покращує захист від компрометації облікового запису, але збільшує складність впровадження. Висновок. Жоден протокол не є універсальним рішенням; найвищий рівень безпеки досягається завдяки поєднанню сучасних протоколів авторизації, багатофакторної автентифікації, шифрування токенів та принципів нульової довіри. Ці висновки можуть бути застосовані розробниками, системними архітекторами та фахівцями з кібербезпеки для проектування та впровадження надійних систем автентифікації та авторизації, здатних вирішувати поточні та нові виклики цифровій безпеці.
Порівняльний аналіз сучасних протоколів автентифікації та авторизації для вебзастосунків
Keywords: authentication; authorization; OAuth; Basic Auth; Single Sign-On; Multi-Factor Authentication; digital security; автентифікація; авторизація; цифрова безпека